2014
DOI: 10.1002/ajpa.22659
|View full text |Cite
|
Sign up to set email alerts
|

To meat or not to meat? New perspectives onNeanderthal ecology

Abstract: Neanderthals have been commonly depicted as top predators who met their nutritional needs by focusing entirely on meat. This information mostly derives from faunal assemblage analyses and stable isotope studies: methods that tend to underestimate plant consumption and overestimate the intake of animal proteins. Several studies in fact demonstrate that there is a physiological limit to the amount of animal proteins that can be consumed: exceeding these values causes protein toxicity that can be particularly dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 290 publications
1
41
0
Order By: Relevance
“…Earlier carbon and nitrogen isotope studies of collagen from Neandertal skeletal remains suggested that they were top-level carnivores obtaining most of their proteins from terrestrial animals, likely medium and large herbivores such as bovids and horses (65), but the Neandertals sampled were mostly from northern open and cold stage environmental settings. These results have been complemented by studies demonstrating a much broader diet, including aquatic foods (fish and molluscs), small animals (including tortoises, birds, and rabbits), and a variety of plant resources across their range (2,66,67). Some of those plant remains were very probably cooked, as suggested by plant microfossils recovered from the calculus of Neandertal teeth (68), a new source of data regarding the food of early hominins (69)(70)(71).…”
Section: Neandertal Ways Of Lifementioning
confidence: 97%
“…Earlier carbon and nitrogen isotope studies of collagen from Neandertal skeletal remains suggested that they were top-level carnivores obtaining most of their proteins from terrestrial animals, likely medium and large herbivores such as bovids and horses (65), but the Neandertals sampled were mostly from northern open and cold stage environmental settings. These results have been complemented by studies demonstrating a much broader diet, including aquatic foods (fish and molluscs), small animals (including tortoises, birds, and rabbits), and a variety of plant resources across their range (2,66,67). Some of those plant remains were very probably cooked, as suggested by plant microfossils recovered from the calculus of Neandertal teeth (68), a new source of data regarding the food of early hominins (69)(70)(71).…”
Section: Neandertal Ways Of Lifementioning
confidence: 97%
“…The study of tooth wear has been an invaluable tool for the reconstruction of dietary and cultural habits in prehistoric populations and extinct human species (e.g., El Zaatari, Grine, Ungar, & Hublin, ; Fiorenza, ; Fiorenza, Bennazi, Tausch, et al, ; Fiorenza et al, ; Fiorenza, Benazzi, & Kullmer, ; Fiorenza & Kullmer, , ; Hinton, ; Molnar, ; Smith, ). Dental wear can be examined at two different scales: macrowear (visible to the naked eye or at low magnification) and microwear (visible only under microscope).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional myth of man the Ice age hunter as "the mighty top carnivore" and keystone species has been eroded by mounting evidence of the importance of plant food in human nutrition (Hardy et al, 2015;Fiorenza et al, 2015). A more probable depiction of AMHs during the second half of the last ice age is that of small bands of foragers who supplemented a mainly vegetarian diet with small game and leftover megafauna carcasses, surviving on the southern fringes of the mammoth steppe due to the association with their dogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have debunked the myth of carnivorous nutrition (Speth & Spielmann, 1983Speth, 2010Henry, Brooks & Piperno 2014;Hardy et al, 2015;Fiorenza et al, 2015;Melamed et al 2016) and indicate an omnivorous diet based on foraging. The recovery of Eurasia mankind from the bottleneck is most likely unrelated to changes in climate or vegetation but rather to Schleidt the invention of new armament, i.e.…”
Section: Humans and Fauna In The Southern Fringes Of The Mammoth Steppementioning
confidence: 99%